2009
DOI: 10.1002/lapl.200910018
|View full text |Cite
|
Sign up to set email alerts
|

The performance of double-clad ytterbium-doped fiber laser with different pumping wavelengths

Abstract: Abstract:The effect of pumping wavelengths on the performance of double-clad Ytterbium-doped fiber laser (YDFL) is experimentally demonstrated. The YDFL is constructed using a fiber Bragg grating as wavelength selective filter in a linear cavity resonator. The YDFL operates at wavelength of 1064.4 nm with a bandwidth of 0.2 nm and signal to noise ratio of more than 30 dB. The efficiency of the YDFL is observed to depend on the absorption cross section spectrum of the YDF. The slope efficiencies of the YDFL are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…That allowed us to deter mine the optimal fiber length of ~5-7 m. We also found that optimal fiber length is not dependent on used pumping wavelength. The gain at 975 nm is slightly higher than at 915 nm because of higher absorption coefficient [20]. But we chose 915 nm for pumping because it provides lower tolerance of gain fluctuation due to pump wavelength variation.…”
Section: Experimental Setup Results and Discussionmentioning
confidence: 98%
“…That allowed us to deter mine the optimal fiber length of ~5-7 m. We also found that optimal fiber length is not dependent on used pumping wavelength. The gain at 975 nm is slightly higher than at 915 nm because of higher absorption coefficient [20]. But we chose 915 nm for pumping because it provides lower tolerance of gain fluctuation due to pump wavelength variation.…”
Section: Experimental Setup Results and Discussionmentioning
confidence: 98%
“…Furthermore, the development of SESAM devices has expanded the applicability in the industry of lasers due to its reliable design and flexibility [23], allowing easyhandle self-starting passive mode-locking by properly choosing the cavity design and controlling the growth parameters of the SESAM semiconductor material [24]. In particular, the advances in ytterbium-doped ultrafast fiber lasers with SESAM technology have demonstrated that Ybdoped fibers are the best option as the gain medium for generation and amplification of SESAM-based mode-locking ultrashort pulses around 1µm wavelength range [25,26] as a consequence of its broad absorption and emission bandwidth, large saturation fluences and high optical conversion efficiencies [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It is a versatile source for pulsed [1][2][3] and continuous-wave [4][5][6] operations, and in combination with fiber components such as fiber based gratings it can be utilized for distributed feedback laser [7] or tunable laser [8].…”
Section: Introductionmentioning
confidence: 99%